The Factors that Influence the Community Preference Using Financial Technology Services in Sharia Financial Institutions - Ahmad Aziz Putra Pratama (Universitas Muhammadiyah Malang, 2020)
This research aims to investigate the factors that influence community preference in using financial technology services in sharia financial institutions. This research uses a descriptive quantitative method through multi-linear regression analysis. The respondents of the research are Rembang people who use sharia fintech services with 1,171 respondents. The sample is selected through incidental sampling. The results show that perceived ease, perceived benefit, and attitude influence the community preference using financial technology services in sharia financial institutions.